2015
DOI: 10.5005/jp-journals-10036-1075
|View full text |Cite
|
Sign up to set email alerts
|

Report of a Rare Case: Ligamentum Flavum Cyst

Abstract: A rare case of ligamentum flavum cyst of the lumbar spine in an elderly male is reported. The patient presented with low backache and features of bilateral radiculopathy of a sudden onset. The cyst was lying in the extradural space. After surgery, the patient reported complete relief of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…6 Complete removal of pseudocystic lesions generally has excellent results. 2,5,6,8,16,17,18,19 Our patient showed complete postoperative resolution of symptoms. She is neurologically intact and symptoms free with 1 year follow up.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…6 Complete removal of pseudocystic lesions generally has excellent results. 2,5,6,8,16,17,18,19 Our patient showed complete postoperative resolution of symptoms. She is neurologically intact and symptoms free with 1 year follow up.…”
Section: Discussionsupporting
confidence: 53%
“…9,10 Complete excision of the ligamentum flavum till its insertion of the cyst assures a minimal rate of recurrence. 5,16 Wildi et al, 19 reported recurrence of the cyst in the remaining ligamentum in two patients within 1 year. While nearly 95% of all operated cysts can be entirely removed, dural adhesions are the major cause of incomplete operative excision.…”
Section: Discussionmentioning
confidence: 99%
“…Most symptomatic cysts usually present with radiculopathy. The history and physical examination findings of these patients may resemble symptoms related to sciatica and disc herniation (11). Typically, cysts can cause radicular pain (97%), sensory (55%) or motor (39%) deficit, Lasèque sign (33%), abnormal reflexes (18%), and rarely present as cauda equina syndrome (1).…”
Section: Discussionmentioning
confidence: 99%
“…There are no pertinent clinical symptoms; however, the spinal canal can impinge upon and displace neural structures and can lead to neurologic symptoms. The majority of symptomatic cysts usually present with radiculopathy, such as sciatica in case of lumbar cysts, and can resemble symptoms related to disc herniation [13] , [14] . Neuroimaging, especially MRI, plays a vital role in the preoperative diagnosis of this condition.…”
Section: Discussionmentioning
confidence: 99%